0259 Newborn beef calves benefit from supplementation of vitamins D and E. (1st October 2016) - Nelson, C. D.; Poindexter, M.; Powell, J. L.; Yelich, J. V.; Bird, S. L.; Stuart, R. L.
Abstract: The objective of this study was to determine the effects of injectable vitamins A, D, and E on fat-soluble vitamin status of beef calves. Sixteen Angus calves from a herd in Minnesota and 17 Angus and Brangus calves from a herd in Florida born in March were randomly assigned to receive no treatment or subcutaneous injection of VITAL-E® Newborn (Stuart Products Inc.; 50, 000 IU retinyl-palmitate, 50, 000 IU vitamin D3, and 500 IU RRR -α-tocopherol/mL of product). Minnesota calves received either no treatment (CON, n = 8) or 5 mL subcutaneous injections of VITAL E-Newborn (ADE, n = 8) within 24 h of birth and serum samples were collected at 0, 2, 7, 50, and 210 d of age. Florida calves received either no treatment ( n = 7) or 4 mL of VITAL E-Newborn ( n = 9) within 24 h of birth and serum samples were collected at 0, 25, 50, and 180 d of age. Serum retinol concentrations were not affected by treatment, but retinyl-palmitate was greater at 2 d of age in the Minnesota ADE vs. CON calves (646 ± 204 vs. 20 ± 1 ng/mL). In contrast, serum 25-hydroxyvitamin D (25(OH)D) concentrations of the Minnesota ADE calves increased from 8.4 ± 1.3 ng/mL at birth to 61.7 ± 3.6 ng/mL at d 7, compared with 5.5 ± 1.3 at birth and 9.8 ± 4.6 at d 7 in CON calves ( P < 0.001). Serum 25(OH)D of Florida ADE calves increased from 9.9 ± 3.3 ng/mL at birth to 36.2 ± 3.9 ng/mL at d 25, compared with 5.4 ± 3.5 and 19.7 ± 4.8 ng/mL in CON calves ( P < 0.05). Serum 25(OH)D was still elevated at 50 d of age in ADE calves in both herds ( P < 0.01; ADE = 38.8 ± 2.3 ng/mL vs. CON = 29.4 ± 2.5 ng/mL), but was the same at weaning near 50 ng/mL. Serum α-tocopherol increased in Minnesota ADE calves from 1.0 ± 0.5 μg/mL at birth to 6.8 ± 0.5 and 5.3 ± 0.5 μg/mL at d 2 and 7, respectively, compared with 0.6 ± 0.5, 1.3 ± 0.5, and 2.4 ± 0.5 μg/mL in Minnesota CON calves at 0, 2, and 7 d of age, respectively ( P < 0.001). Serum α-tocopherol was similar between Florida ADE and CON calves with averages near 0.8 μg/mL at birth and 2.5 μg/mL at 25 d of age. In conclusion, supplementation of newborn beef calves with VITAL-E Newborn increases serum 25(OH)D and α-tocopherol concentrations and overcomes deficiences in vitamins D and E of the young calf.